Implementation of the Financing Model in Improving the Performance of the Principal of the Case Study at SDN Loa 1, Paseh District - H. Soro , Suharyanto; Fitriani, Seni; Yuningsih , Yuyun (Civiliza Publishing, Indonesia., 2025)
Education has a strategic role in the development of a nation, especially in the era of globalization and digital transformation that demands innovation in education management. This context refers to education financing which is considered a vital instrument to support the improvement of the quality of school leadership. The theoretical framework adopted includes the principles of education management and financial governance theory, thus providing a comprehensive understanding of the financing mechanism and its impact on leadership effectiveness. This study aims to find a financing model based on transparency, integration, and sustainability in improving the performance of school principals. This study highlights the strategic role of fund allocation in managerial decision making and program innovation at SDN Loa 1, Paseh District. A case study approach with qualitative methods was used in this study. Data were collected through observation methods, in-depth interviews, and relevant financial documents and financing policies. The results of the study indicate that the implementation of a structured financing model significantly improves the principal's ability to manage the budget, design education programs, and make strategic decisions; Several obstacles, such as limited resources, uneven distribution of funds, and weaknesses in internal supervision that hinder the optimization of fund use. The conclusion of this study is that an effective financing model can be the main catalyst for improving school leadership performance.